Development and Characterization of Herbal Nano Particulate herbal tablet of Euphorbia thymifolia l. for treatment of Diabetes - K.G. Bhutkar,; P. Balaji, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The study on Euphorbia thymifolia focused on the authentication, extraction, and analysis of its bioactive compounds. The plant was collected and authenticated from the Western Ghats, and a pharmacognostic study revealed key morphological and microscopic features, including anomocytic stomata and fibrous roots. Various extracts were prepared using solvents like hexane, chloroform, ethyl acetate, ethanol, and water, with the ethanol extract yielding the highest percentage. Preliminary phytochemical screening indicated the presence of bioactive compounds such as alkaloids, glycosides, flavonoids, tannins, and steroids. Thin Layer Chromatography (TLC) further confirmed these findings, identifying several bioactive compounds in the ethanol extract. In vitro studies evaluated the extracts' antidiabetic potential, revealing significant alpha-amylase inhibition, particularly in the ethanol and hexane extracts, showing inhibitory activities of 73.33% and 70.00%, respectively. Subsequently, herbal nanoparticles were prepared using the nano-precipitation method with the ethanol extract of Euphorbia thymifolia, resulting in nanoparticles with a yield of 73.12%, a particle size of 95.6 nm, and a zeta potential of -19.5 mV. Stability studies over three months showed minimal changes in particle size, zeta potential, and entrapment efficiency. Additionally, nanoparticles containing an isolated compound (A4 fraction) demonstrated excellent stability, with particle size and zeta potential remaining stable and entrapment efficiency slightly improving. These results highlight the potential of Euphorbia thymifolia extract and its nanoparticles for pharmaceutical applications, particularly in antidiabetic therapy.